Loktak Floating Elementary School A Beacon of Hope for School Dropouts of the Champu Khangpok Floating Village - Yaipharemba, I. (JOURNAL OF INDIAN EDUCATION, 2017)
Right to Education is for every individual, regardless of caste, creed, age or gender. An individual must be empowered by education irrespective of circumstances. When a child picks up a pencil, it exemplifies as one more responsible person in the making. Pursuing an education is not only practically gaining knowledge, but also earning dignity to live as a free person in the society. Without the value of education, a civilisation is near to be doomed, hence, getting a formal education encourages a culture to the very peak of development and prosperity. This is a study of Loktak Floating Elementary School, a community initiative school for dropout children in Langolsabi Leikai of Champu Khangpok floating village in the northern part of Loktak Lake, which elucidates a belief of enlightenment among many underprivileged children and others. The school was formally inaugurated on the occasion of World Wetlands Day, 2 February 2017, though it had already started functioning since December 2016. Presently, the school accommodates 25 students (Classes I–III) and two teachers from the community. It is envisaged to cater to the needs of illiterate adults as well. The idea was to establish the school surface considering the high dropout rate of children living in the floating villages when the Loktak Development Authority removed more than 770 floating huts as per the Loktak Lake (Protection) Act 2006, five years ago, resulting in extensive displacement of the fishing community.